APLIKASI STREAMING MULTIMEDIA PADA M-DOCTOR DENGAN SELULAR WCDMA - Santoso, Gatot; Sutanta, Edhy; Wibowo, Samekto (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Information technology and ielecommunications to the Internet becomes the main priority in the development of world progress. These developments provide new break-through in health care services mobile using mobile IT devices or socalled mobile doctor (m-doctor). M-doctor has some excess capacity for health care services that can be accessed anytime, anywhere, by anyone. The problems that still esist on still on m-doctor is that the lack of hardware and platforms that required by the system design and ease of access. One also needs a special study of each section dealing with the existing m-doctor in order to get comfortable for the user. The aim of this study is to address the issue by using streaming multimedia as content that can offer a more clear and specific infor-mation. Streaming multimedia services m-doctor require internet connection and good access, and also requires capable hardware to enjoy the overall bias with good services by using phones that support streaming multimedia mobile facilities. Expected results of this study is a software-based content cellular WCDMA, and the main target is to design m-doctor with streaming multimedia services.